Frost Susceptibility of Five Almond [Prunus dulcis (mill.) D.A. Webb] Cultivars Grown in North-Eastern Morocco as Revealed by Chlorophyll Fluorescence. Issue 4 (2nd October 2017) - Sakar, El Hassan; El Yamani, Mohamed; Rharrabti, Yahia
ABSTRACT: Almond [ Prunus dulcis (Mill.) D.A. Webb] is one of the most important nut crops worldwide. It requires chilling during winter to break dormancy and develop fruiting buds. However, late winter chilling and early spring frosts may damage the reproductive tissues leading to productivity reduction. In the present work, we evaluated the frost susceptibility by means of chlorophyll fluorescence in flower buds of almonds cultivated in two different sites in Morocco: Aknoul in the north and Sidi Bouhria in the east. Five widely grown almond cultivars, namely Marcona, Fournat de Brézenaud, Ferragnès, Ferraduel, and Tuono, were involved in this study. Flower buds were incubated in temperatures of –3, –2, –1, 0, and 25 °C during 24 h and thereafter the Fv/Fm ratio was measured at the ovary zone. Combined analysis of variance showed that cultivar was the major source of variability, while site and cultivar by site interaction effects were of lesser extent and explained together less than 20%. At 25 °C, all cultivars displayed higher scores of Fv/Fm ratio. By decreasing temperature of incubation, this ratio decreased proportionally. Kinetics of chlorophyll fluorescence in response to the frost treatment followed two patterns: A linear decrease translated by frost susceptibility for late-flowering cultivars Ferragnès and Ferraduel, and quadratic curve with an inflection point at –1 °C indicating a chilling tolerance for Tuono and the early-flowering cultivars Marcona and Fournat de Brézenaud. However, Ferragnès and Ferraduel (with later flowering date) are not likely to be affected by low temperatures at the end of spring when there is no risk of frost.